More load less harm? Perceived harmfulness of daily activities in weightlifters and powerlifters - Syrett, J.; Liew, B. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction. Weightlifting (WL) and Powerlifting (PL) are popular strength-based sports, which are associated with large spinal tissue loads (1,2). Low back pain (LBP) is one of the most common disorders incurred by WL and PL (3). Fear of movement has been thought to be a risk factor for the onset and persistence of LBP (4), but this has only been investigated in the general population. Whether similar levels of fear exist in a cohort of athletes who frequently expose themselves to high and repetitive spinal loads is uncertain. In addition, the predictors of fear in people who perform WL and PL are unknown.